2021
DOI: 10.1002/ibra.12001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of norepinephrine on microglial neuroinflammation and neuropathic pain

Abstract: Norepinephrine (NE) is an important neurotransmitter in the central nervous system. NE is released from locus coeruleus neurons and is involved in a variety of physiological and pathological processes. Neuroinflammation is a common manifestation of many kinds of neurological diseases. The activation of microglia directly affects the status of neuroinflammation. Several kinds of adrenergic receptors, which anchor on microglia and can be regulated by NE, affect the activation of microglia and neuroinflammation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Neuropathic pain is often accompanied by neuroinflammation, and relieving neuroinflammation will effectively reduce pain. 29,30 Similar to the results of our previous study, 3 in the present study, we found that CCI mice had significant spinal cord neuroinflammation with increased expression of inflammatory cytokines TNF-α, IL-1β, and IL-6. We used immunofluorescence and found that TNF-α and IL-1β colocalized with microglia.…”
Section: Increased Expression Of Psd-95 In Sdh Affected Phagocytic Mi...supporting
confidence: 91%
“…Neuropathic pain is often accompanied by neuroinflammation, and relieving neuroinflammation will effectively reduce pain. 29,30 Similar to the results of our previous study, 3 in the present study, we found that CCI mice had significant spinal cord neuroinflammation with increased expression of inflammatory cytokines TNF-α, IL-1β, and IL-6. We used immunofluorescence and found that TNF-α and IL-1β colocalized with microglia.…”
Section: Increased Expression Of Psd-95 In Sdh Affected Phagocytic Mi...supporting
confidence: 91%
“…However, research has found that sympathetic nerves are involved in the maintenance of many kinds of chronic pain 4 . Therefore, inhibition of sympathetic hyperexcitability may improve the therapeutic effect, which may be related to the involvement of sympathetic nerves in regulating glial inflammation 5 . Among them, intervention of stellate ganglion (SG) is effective for pain in the head, face, neck, upper limbs, or upper chest.…”
Section: Introductionmentioning
confidence: 99%
“…4 Therefore, inhibition of sympathetic hyperexcitability may improve the therapeutic effect, which may be related to the involvement of sympathetic nerves in regulating glial inflammation. 5 Among them, intervention of stellate ganglion (SG) is effective for pain in the head, face, neck, upper limbs, or upper chest. In this review, we summarize the clinical evidence available for the effectiveness of stellate ganglion intervention (SGI), and demonstrate clinical applications of SGI.…”
Section: Introductionmentioning
confidence: 99%
“…It's assumed that NE extracellular levels are reduced since NE tissue levels are depleted after DSP-4 treatment; however, some reports have challenged this idea, showing that DSP-4 treatment signi cantly increases extracellular levels of NE in the brain [19,[26][27][28]. This could explain our results showing DSP-4-mediated protection in the context of hα-SYN mediated neurotoxicity since increased NE signaling in the brain is associated with a reduction in neuroin ammation and neuronal degeneration in vitro and in vivo [48,49]. This hypothesis is supported by the observation that blocking the β-ARs using propranolol, reverses DSP-4 protection of dopaminergic neurons after hα-SYN overexpression.…”
Section: Discussionmentioning
confidence: 75%